2018
DOI: 10.1515/bmt-2017-0012
|View full text |Cite
|
Sign up to set email alerts
|

Software design and implementation concepts for an interoperable medical communication framework

Abstract: The new IEEE 11073 service-oriented device connectivity (SDC) standard proposals for networked point-of-care and surgical devices constitutes the basis for improved interoperability due to its independence of vendors. To accelerate the distribution of the standard a reference implementation is indispensable. However, the implementation of such a framework has to overcome several non-trivial challenges. First, the high level of complexity of the underlying standard must be reflected in the software design. An e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In this work, scholars discuss how to deal with these challenges and develop a descriptive model to determine key strategies. But the experiment did not mention what the new method is, and the concept is too vague [ 3 ]. Lacey and Donne found that ankle joint injuries not only lead to the destruction of static and dynamic balance, but also result in wasting a lot of exercise time, affecting athletes' daily activities, and may put athletes at greater risk of injury.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, scholars discuss how to deal with these challenges and develop a descriptive model to determine key strategies. But the experiment did not mention what the new method is, and the concept is too vague [ 3 ]. Lacey and Donne found that ankle joint injuries not only lead to the destruction of static and dynamic balance, but also result in wasting a lot of exercise time, affecting athletes' daily activities, and may put athletes at greater risk of injury.…”
Section: Introductionmentioning
confidence: 99%
“…For the sake of simplicity, this section describes only the constructive part, leaving the process of requirements gathering aside (a more detailed overview is given in [6]). Most of the functional requirements are defined by the SDC standard documents.…”
Section: Methodsmentioning
confidence: 99%
“…In a second approach, developed in Java, we made generous use of available components to quickly generate working results while accepting possible risks of adapting to an unknown software and changing it in order to fulfil all needed requirements. A more detailed description of the first approach is available in [6]. Here, we present a summarized view and focus on the comparison with the second approach.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the latency of an OR.NET based tracking system, a setup has been selected with two real time Linux systems as consumer and provider, an atracsys fusionTrack500 tracking camera, and a single infrared (IR) LED, used as a single fiducial. The consumer and provider software was implemented using the SDCLib/C by SurgiTAIX AG, Herzogenrath, Germany (Besting 2018;www.surgitaix.com). Details of the underlying service oriented architecture are described in (Ibach 2008;Kasparick 2015).…”
Section: Methodsmentioning
confidence: 99%